Impact of Thyroid Dysfunction in the General Population of Bhopal, Madhya Pradesh (Homoeopathy for All, 2025)
Thyroid dysfunction has become  increasingly common in Indian  urban populations, including Bhopal,  Madhya Pradesh. Disorders such as  hypothyroidism and hyperthyroidism  can severely affect metabolism,  mental health, pregnancy outcomes,  and cardiovascular function. This  study examines the prevalence, risk  factors, and health implications  of thyroid dysfunction among the  general population in Bhopal. Based  on existing epidemiological data,  hospital records, and public health  surveys, the research identifies young  women, pregnant individuals, and  those with metabolic disorders as  high-risk groups. The study highlights  the urgent need for public health  interventions, including routine  screening, improved iodine nutrition,  and targeted awareness programs in  the region.
Keywords: Thyroid Dysfunction; Hypothyroidism; Bhopal, Public Health; Iodine Deficiency; Madhya Pradesh